IMPROVING STUDENTS' WRITING SKILL USING PYRAMID STRATEGY (A CLASSROOM ACTION RESEARCH AT THE FIRST YEAR OF MTS MUHAMMADIYAH BLIMBING SUKOHARJO) - RIFA'I, BACHTIAR (2010)
This study is aimed to describe the process of improving student's writing skill using pyramid strategy in MTs Muhammadiyah Blimbing Sukoharjo and find whether teaching writing using pyramid strategy can improve the students' writing ability. The result of the study is expected to contribute to the teaching learning of writing. The study was implemented in MTs Muhammadiyah Blimbing Sukoharjo, especially class VIA using action research. The researcher took 25 students as the subject of research. The object of the research was implementation of pyramid strategy in MTs Muhammadiyah Blimbing Sukoharjo. The researcher gets the data of this research from teaching, event, informant, and document. The techniques of collecting data are observation, test, document and interview. The result of the study shows that pyramid strategy technique is appropiate and quite effective for teaching writing. The students' motivation improves and maintains in teaching learning process of writing. By using this technique, the students are capable of writing a composition easily. They are enthusiasthic, interested, and motivated in the classroom, because the teacher used kinds of interesting material such as story to encourage the students to involve in teaching learning process.